2011
DOI: 10.1007/s11259-010-9456-4
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus granulosus: Immunoprotection accompanyied by humoral and cytokine response against secondary hydatidosis in mice immunized with rEg.myophilin

Abstract: rEg.myophilin showed a effectively protective immunity, which may attribute to: (1) IgGs and IgE-mediated humoral immune response, as well as cell-mediated immunity which was marked by IFN-γ. (2) IL-4 assists to stimulate type transformation of IgE which plays an important role in Eosinophils-related anti-parasite immunity. (3) Immunosuppressive effect (marked by IL-10), the key obstacle to clean of parasites in the patient, was inhibited in the rEg.myophilin group compared with control groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Furthermore, the immune response and the induced immunoprotection of recombinant Eg.myophilin (rEg.myophilin) were investigated using an experimental model of hydatidosis in mice challenged with E. granulosus protoscoleces (14). It is also known that cytokines and serum antibodies serve an important role in CHD.…”
Section: Cystic Hydatid Disease (Chd) Is a Results Of Infection Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the immune response and the induced immunoprotection of recombinant Eg.myophilin (rEg.myophilin) were investigated using an experimental model of hydatidosis in mice challenged with E. granulosus protoscoleces (14). It is also known that cytokines and serum antibodies serve an important role in CHD.…”
Section: Cystic Hydatid Disease (Chd) Is a Results Of Infection Withmentioning
confidence: 99%
“…In addition, rEg.myophilin has been reported to show an effectively protective immunity in mice (14). However, these experiments present two deficiencies: E. granulosus protoscoleces were intraperitoneally inoculated (secondary infection) due to the experimental condition at the time of the experiments, and thus the natural infection mode was peroral with E. granulosus eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the 14-3-3 protein (15), myophilin (16), ferritin (17) and P29 (18) that are secreted by E. granulosus exhibit marked immunogenic properties. The aim of the present study was to determine whether immunization with rEgGST was able to induce effective protective immunity when compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the native antigen model is not suitable for inducing protective immunity due to an increase in IL-10 levels that results in a Th2 response to different antigens such as EgA31 and EgTrp (Fraize et al 2005). Increased levels of IFN-γ and IL-4 have been observed in mice immunised with recombinant myophilin (Sun et al 2011). However, these proteins have the ability to produce a mixed Th1-Th2 response and the presence of a Th2 response may render the host capable of tolerating the presence of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Eg95 induced a significant immune response in sheep (Woollard et al 2000). Other reports discussed the roles of P14-3-3 (Siles-Lucas et al 2008), recombinant myophilin (Sun et al 2011) and phosphoglucose isomerase as protective antigens. However, none of these proteins has been found to induce relevant protectivity against E. granulosus in its definitive host.…”
mentioning
confidence: 99%